Acute mesenteric ischemia: a review of 50 cases - Ranchordás, Sara; Cunha, Cátia; Roque, Rita; Féria, Luís; Maio, Rui (International Surgery Journal, 2019)
Background: Acute mesenteric ischemia is a rare but highly lethal cause of abdominal pain. Diagnosis should be prompt to ensure early treatment and avoid progression of the disease. The aim of the study was to describe the population presenting with acute mesenteric ischemia submitted to surgery, evaluate their outcome and determine possible predictors of mortality. Methods: Retrospective analysis of all patients who underwent surgery due to mesenteric ischemia between May 2013 and January 2015. A total of 50 patients were included. Pre-operative patient risk factors, diagnostic and surgical approach, post-operative complications and outcome were analysed. Statistical analysis was performed using SPSS v. 20. Univariable analysis was performed using T student and chi square tests. Results: Mean age was 79 years. Most patients (n=43) had cardiovascular risk factors. Clinical and laboratory studies findings were non-specific. During surgery, 28% were found to have extensive ischemia. Exclusive exploratory laparotomy was done in 11 cases due to extensive ischemia. Thrombectomy was performed in 6 cases. Eleven patients were submitted to reoperation. In-hospital mortality was 68% (n=34). Patients who died had more frequently systemic findings and extensive ischemia. Patients with extensive vs. segmental ischemia were also compared and no statistically significant differences regarding preoperative findings were found. Mortality was significantly higher in patients with extensive ischemia. Conclusions:Timely diagnosis and treatment are essential to improve the outcome of AMI but tools to perform this are still lacking. Mortality remains high, especially when ischemia is extensive at the time of surgery.